Using Web-based support for campus-based open learning: lessons from a study in dental public health - Ruth Holt; Martin Oliver; Claire McAvinia (Association for Learning Technology, 2002)
There has been much written about the use of the Web in higher education, much of which advocates its use as an effective way of supporting learning, particularly in terms of the desirability of features such as flexibility and the value of online discussions. In this paper, a case study is described which calls some of this received wisdom into question. The study also explores wider issues of curriculum design, particularly in terms of the role of assessment and of self-assessment, both of which played a crucial role in the course. Unlike many studies, then, the purpose of this paper is not to demonstrate the success of a particular approach or to advocate particular forms of practice, but instead to highlight the shortcomings of existing guidelines for curriculum development in this area. This suggests that further inquiry into this form of education is required – and in particular, inquiry that pays detailed attention to the backgrounds of learners, and involves close study of their experiences.